Study of coalescence-induced droplet jumping during phase-change process in the presence of noncondensable gas. (May 2020) - Shi, Y.; Tang, G.H.; Shen, L.Y.
Highlights: Coalescence-induced droplet jumping during phase-change process is studied with lattice Boltzmann method. The effect of large amount of noncondensable gas is taken into account and studied. The coalesced droplet diameter and jumping height decrease with increase of noncondensable gas fraction. The hybrid wettability surface is beneficial to enhance condensation heat transfer. A higher subcooling degree accelerates droplet growth and promotes droplet jumping. Abstract: The coalescence-induced condensation droplet jumping on subcooled surface is simulated using the pseudo-potential lattice Boltzmann method, especially the coupled phase-change condensation process and the large amount of noncondensable gas are taken into account. The method is validated by the density distribution of two components inside and outside droplet, the contact angle of droplet spreading on wettability surface as well as the condensing droplet diameter under various noncondensable gas fractions. The effects of noncondensable gas fraction, wettability as well as subcooled surface temperature on condensation heat transfer during droplet nucleation, growth and departure are investigated. The results indicate that the increase of noncondensable gas fraction causes higher resistance to condensable gas diffusion, leading to a reduction of local heat flux near the triple-phase contact line area. Correspondingly, both the coalesced droplet diameter and its maximum jumping height decrease with the increase of noncondensable gas fraction. Compared to the hydrophobic surface, the hydrophilic surface is more favorable for attracting condensable gas and results in a faster onset of nucleation and a higher droplet condensing rate. Moreover, a higher surface subcooling degree accelerates droplet growth and promotes droplet jumping to a higher height. The energy conversion of the removal droplet is also examined. The present work not only demonstrates the capacity of the lattice Boltzmann method but also sheds light on the mechanism of coalescence-induced condensation droplet jumping in the presence of noncondensable gas.